2018
DOI: 10.1136/jmedgenet-2018-105745
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive genomic variation profiling of cervical intraepithelial neoplasia and cervical cancer identifies potential targets for cervical cancer early warning

Abstract: BackgroundTo better understand the pathogenesis of cervical cancer (CC), we systematically analysed the genomic variation and human papillomavirus (HPV) integration profiles of cervical intraepithelial neoplasia (CIN) and CC.MethodsWe performed whole-genome sequencing or whole-exome sequencing of 102 tumour-normal pairs and human papillomavirus probe capture sequencing of 45 CCs, 44 CIN samples and 25 normal cervical samples, and constructed strict integrated workflow of genomic analysis.ResultsMutational anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 46 publications
7
42
0
Order By: Relevance
“…Recent studies have identified several oncogenic factors involved in promoting CC progression, including HMGA1, BAP31, KLF5, Fibulin 3, mirRNA-196a, miR-146b-3p, and various long non-coding RNAs (Figure 3) [22,23,24,25,26,27,28]. On the other hand, the CC suppressor role of miR-27a, miR-424, mir140-5p, and mir-328 were also demonstrated [29,30,31,32]. In parallel, high throughput genome sequencing of progressive CC specimens from 120 women identified novel somatic mutations in FAT1 , MLL3 , MLL2 , and FADD (Figure 3) [32].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have identified several oncogenic factors involved in promoting CC progression, including HMGA1, BAP31, KLF5, Fibulin 3, mirRNA-196a, miR-146b-3p, and various long non-coding RNAs (Figure 3) [22,23,24,25,26,27,28]. On the other hand, the CC suppressor role of miR-27a, miR-424, mir140-5p, and mir-328 were also demonstrated [29,30,31,32]. In parallel, high throughput genome sequencing of progressive CC specimens from 120 women identified novel somatic mutations in FAT1 , MLL3 , MLL2 , and FADD (Figure 3) [32].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the CC suppressor role of miR-27a, miR-424, mir140-5p, and mir-328 were also demonstrated [29,30,31,32]. In parallel, high throughput genome sequencing of progressive CC specimens from 120 women identified novel somatic mutations in FAT1 , MLL3 , MLL2 , and FADD (Figure 3) [32]. In addition, this study identified HPV integration breakpoints in 97.8% of CCs, 70.5% of cervical intraepithelial neoplasias (CINs), and 42.8% of HPV + normal cervical epithelium [32].…”
Section: Introductionmentioning
confidence: 99%
“…In 99 EBD adenocarcinomas, CREBBP rearrangement was found in one case (1%) and MLL2 alterations in four cases (4%), while to our knowledge alterations in the remaining four genes, NOTCH1, FAT1, CTCF, and MAGI2 have not been reported in EBD adenocarcinomas. In contrast, aberrations in FBXW7, NOTCH1, FAT1, CREBBP, and/or MLL2 have been reported in SCC of the esophagus, lung, uterine cervix and head and neck . In primary esophageal SCC and in metastatic SCC of the anal canal, MLL2 was among the most frequently mutated genes, while in a series of 20 primary anal SCCs, FBXW7 (15%), FAT1 (15%), and NOTCH1 (10%) were found most often mutated.…”
Section: Discussionmentioning
confidence: 89%
“…In SCC of the uterine cervix, FBXW7 represented the second most frequently altered gene, and it was suggested that this might represent one of the driver mutations in this neoplasm . The same study found also alterations in FAT1, MLL2, NOTCH1, and CREBBP in SCC of the cervix, but neither these genes nor FBXW7 were mutated in their CIN specimens . Taken together, these studies indicate that some molecular features of EBD‐SCC, but far from all, are shared with SCC from other organs.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation